London Levellers in the English Revolution: the Chidleys and Their Circle - Gentles, Ian (The journal of ecclesiastical history, 1978)
‘There is one Katherine Chidly an old Brownist, and her sonne a young Brownist, a pragmaticall fellow, who not content with spreading their poyson in and about London, goe down into the Country to gather people to them… Katherine Chidly and her sons Books (for the mother and the son made them together, one inditing, and the other writing) are highly magnified, and the brasen-faced audacious old woman resembled unto Jael …’.